Pengaruh Kebijakan Moneter Terhadap Inflasi di Indonesia - M. Rasyidin; M. Saleh; Hakim Muttaqim; Nova Nova; Cut Khairani (Journal of Business and Economics Research (JBE), 2022)
Monetary policy is a factor that affects of economic activities of a country. Monetary policy refers to the use of monetary indiactors suc as interest rates, money supply, and exchage rate under the control of the central bank in order to achieve economic stability. Economic stability serves to maintain a balance of costs or prices, so that excessive inflation occurs. This study examines the effect of monetary policy indicators on inflation. Time series data using the analysis model equation of the multiple linear regression analysis method. The study used a time series yearly data spanning 1991 t0 2020. The results showed that interest rates and money supply had a negative and significant effect on inflation, while the exchange rate had a positive and significant effect on inflation